PENGARUH KEMAMPUAN PERSONEL AIR TRAFFIC CONTROL TERHADAP PELAYANAN LALU LINTAS UDARA UNIT TOWER DAN APPROACH DI BANDAR UDARA INTERNASIONAL PATTIMURA AMBON - Moh Afif Zain Ardiyanto; Laila Rochmawat; Raharjo Tedjo Prasetyo3 (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Air traffic service is a service that plays an important role in creating safety and smooth air traffic flow. To achieve this goal, it is necessary to be supported by the ability of competent human resources. From this it can be concluded that the ability of each personnel in making decisions can affect safety, smooth air traffic flow and flight efficiency. This study aims to obtain an overview of whether there is an influence between the ability of Air Traffic Control personnel and the air traffic services provided at Pattimura International Airport, Ambon. The research method used is quantitative. Data collection is in the form of a documentation study containing the results of ATC personnel performance checks and questionnaires distributed to the sample, then data processing requirements are carried out in the form of validity, reliability, normality, and associative hypothesis testing including correlation. The object of research is air traffic control personnel at Pattimura International Airport, Ambon. The results showed that the ability of ATC personnel to air traffic services had an effect of 41.3% in the first semester and 50.6% in the second semester, which means an increase of 9.3%. And has a significant relationship to the performance of air traffic guides with a correlation coefficient of 90.711, which means that the associative effect between these variables is strong. The average value of performance check, the performance of ATC personnel in the Approach Control Unit (APP) and Aerodrome Control Tower (TWR) Ambon is in the good category, namely (87.6%) in semester 1 and (88.2%) in semester 2 with an average positive increase of 0.504, based on the questionnaire, air traffic services at the Approach Control Unit (APP) and Aerodrome Control Tower (TWR) Ambon are in the good category (86.1%). So it can be concluded that the higher the score obtained, the better the air traffic service. it is recommended to further improve air traffic services and the capabilities of the ATC personnel themselves.